High-Salt Loading Downregulates Nrf2 Expression in a Sodium-Dependent Manner in Renal Collecting Duct Cells - Liu, Mi; Deng, Mokan; Luo, Qimei; Dou, Xianrui; Jia, Zhanjun (Frontiers in Physiology, 2020)
Background: High salt intake is associated with both oxidative stress and chronic kidney disease (CKD) progression. Nuclear factor E2-related factor 2 (Nrf2) is a transcriptional factor regulating the antioxidant and detoxifying genes to potently antagonize oxidative stress. This study examined the effect of high salt loading on the expression of Nrf2 in kidney. Methods: Mice were treated with acute salt loading, and Nrf2 expression in the kidney was detected by Western blotting and immunostaining. Reactive oxygen species (ROS) levels in the kidney were measured using dihydroethidium (DHE) staining. In vitro, mpkCCD cells were cultured in high osmolality medium by adding sodium chloride (NaCl), sodium gluconate (Na-Glu), choline chloride (Choline-Cl), or mannitol. Then Nrf2 and its target genes were measured. Results: Nrf2 protein in renal cortex and medulla tissue lysates was significantly downregulated after acute salt loading. Immunofluorescence data showed that Nrf2 was mainly located in collecting duct principal cells evidenced by co-staining of Nrf2 with AQP2. Contrasting to the reduced Nrf2 expression, ROS levels in the kidney were significantly increased after salt loading. In vitro, the Nrf2 protein level was downregulated in mpkCCD cells after NaCl treatment for 24 hours. Interestingly, sodium gluconate had a similar effect on downregulating Nrf2 expression as NaCl, whereas neither Choline-Cl nor mannitol changed Nrf2 expression. Meanwhile, the mRNA levels of Nrf2 target genes were downregulated by NaCl and/or sodium gluconate, while some of them were also regulated by Choline-Cl, indicating a more complex regulation of these gene under a high salt condition. Finally, we found the downregulation of Nrf2 caused by NaCl was not affected by N-acetylcysteine (NAC), spironolactone or NS-398, suggesting other mechanisms mediating Nrf2 downregulation caused by high salt challenge. Conclusion: High salt downregulated Nrf2 mainly via a sodium-dependent manner in kidney collecting duct cells, which might contribute to the excessive renal oxidative stress and CKD progression.